(3eYZfj GddHjH Yf cJH GdCYGQjHs - (3GdCfUGQj GdeUQj, CHh eMeO, GHf gTGe, LeGd GdOjf, YHOGddg Hf jhSa Hf CMeO Hf YHOGddg, J (B761 (3g`s ((3jhSa Hf jhSa Hf eMeO Hf jYbhH GdTGaYjs)
(3ChdgG (B:s
(3CeG HYO MeOG ddg Ydi CaVGdg hdeG ef Gddg JYGdi Ydj SfI (B756(3g` HeYGhOI MQe Gddg hGdeLGhQI aj NjQ HdGO Gddg hVYJ gPG GdJUfja Ydi CMSf EMcGe hJQUja hJJHYJ ajg ebadGJ eSGFd GdEYQGH aGaJJMJgG heYVdGJ JSJTcdgG GdWdGH aChVMJgG hfbMJgGs
(3BNQgG (B:s
(3GdYGTQ GYWG CaYd aj GdJYLH Mce CaYd GdJaVjd aj LhGR GdJUZjQ hCYWG CaYd GdJaVjd Mce CaYd ajGdJYLH aj Cfg dG jQaY GdXGgQ hbO eQ Pde hdh PcQJ CMQa GdLQ ONhd HYVgG Ydi HYV aj eYfGg dLGA ef Pdc CeKdI cKjQI hgPG BNQ eG JjSQs
(3ebGHdI Ydi fSNJjf hebQhAI Ydi GdTjN CHj GdYHGS CMeO Hf RjO GdMfHdj HbQGAI eGdcgG jhSa Hf eMeOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B: 4 / 147s
(3eYLe GdeDdajf(B: 2 / 305s
(3cTa GdXfhf(B: 2 / 1752s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs